Model Pemberlajaran Geraj Dasar Manipulatif Pada Siswa Sekolah Dasar Kelas 3 - David Elsaver; Samsudin Samsudin; Oman Unju Subandi (Jurnal Porkes, 2026)
The low level of basic manipulative throwing and catching skills among elementary school students, especially those in grade 3, is a major problem in physical education learning. This study aims to develop and test the effectiveness of a systematic and enjoyable game-based learning model for basic manipulative skills. The research method used was Research and Development (R&D) by adopting the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The research subjects consisted of 30 third-grade students at Tadika Puri Elementary School, East Jakarta. Data were collected through observation, in-depth interviews with teachers, and skill tests using standardized instruments. Data analysis was performed using a paired sample t-test statistical test. The research results produced a final product in the form of 30 variations of learning models (15 for throwing and 15 for catching) that have been validated by experts. The effectiveness test showed a very significant increase in throwing skills (from an average of 27.77 to 31.07) and catching skills (from 27.50 to 30.73) with a significance value of p < 0.001. In conclusion, the game-based manipulative basic movement learning model developed has been proven to be statistically and practically effective in improving students' motor skills, so it can be used as an alternative innovative PJOK learning model in elementary schools.